A simple surface mapping technique using laser triangulation method - Tjio, Hok Hoo; Arshad, Mohd Rizal (Universiti Sains Malaysia, 2000)
The system employs a solid-state laser with internal beam conditioning for range to a target by utilising the triangulation technique. The grating line was made from a transparent material with a width of one pixel set using a computer programme. A fixed black and white (BIW) camera together with a frame grabber DT-3135 was used to acquire the 2D image of the object.